How to Improve Sports Fans' Attitudes Toward the Sponsor Through Brand Management? A PLS and QCA Approach - Dos-Santos Manuel Alonso; Alguacil Mario; Pérez-Campos Carlos; Velasco-Vizcaíno Franklin (Sciendo, 2023)
The aim of the article is to explain attitudes towards the sponsors of a sporting event from brand management, especially considering the perceptions of congruence with the sponsor, quality, value, and two less common variables of innovation and popularity. The analysis has been carried out using two methodological approaches: a Partial Least Squares (PLS) model and a Qualitative Comparative Analysis (QCA). PLS results indicate that congruence, innovation and popularity significantly predict attitudes towards the sponsor, explaining up to 61% of it. On the other hand, QCA analysis shows nine interactions capable of producing the expected result, where congruence, quality innovation and popularity have shown a relevant role. This study has implications at a theoretical and practical level, contributing to understanding consumer behaviour in the context of sporting events and providing marketing managers with valuable information to help improve the performance of their sponsorships.